Bifidobacterium animalis: the missing link for the cancer-preventive effect of Gynostemma pentaphyllum - Weilin Liao; Imran Khan; Guoxin Huang; Shengshuang Chen; Liang Liu; Wai Kit Leong; Xiao Ang Li; Jianlin Wu; W. L. Wendy Hsiao (Gut Microbes, 2021)
Colorectal cancer (CRC) ranks the third most common cancer type in both men and women. Besides the known genetic and epigenetic changes in the gut epithelial cells, we now know that disturbed gut microbes could also contribute to the onset and progression of CRC. Hence, keeping a balanced gut microbiota (GM) has become a novel pursue in the medical field, particularly in the area of gastrointestinal disorders. Gynostemma pentaphyllum (Gp) is a dietary herbal medicine. In our previous study, Gp saponins (GpS) displayed prebiotic and cancer-preventive properties through the modulation of GM in ApcMin/+ mice. However, the specific group(s) of GM links to the health effects of GpS remains unknown. To track down the missing link, we first investigated and found that inoculation with fecal materials from GpS-treated ApcMin/+ mice effectively reduces polyps in ApcMin/+ mice. From the same source of the fecal sample, we successfully isolated 16 bacterial species. Out of the 16 bacteria, Bifidobacterium animalis stands out as the responder to the GpS-growth stimulus. Biochemical and RNAseq analysis demonstrated that GpS enhanced expressions of a wide range of genes encoding biogenesis and metabolic pathways in B. animalis culture. Moreover, we found that colonization of B. animalis markedly reduces the polyp burden in ApcMin/+ mice. These findings reveal a mutualistic interaction between the prebiotic and a probiotic to achieve anticancer and cancer-preventive activities. Our result, for the first time, unveils the anticancer function of B. animalis and extend the probiotic horizon of B. animalis.